An integrated approach on msmes financial literacy - Nikolaos Daskalakis; Efstathios Karpouzis; Dimitrios Giakoulas (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The main objective of this paper is to suggest an integrated approach of assessing the level of financial literacy of MSMEs, combining quantitative data derived by the use of the OECD/INFE (2019) questionnaire, and qualitative data via designing focus groups to discuss the survey results with various stakeholders and get policy recommendations. Design/methodology/approach: We apply a two-stage methodology; we first use the specifically designed OECD/INFE (2019) questionnaire, and we second apply qualitative focus-group analysis methodology, where we create groups of stakeholders to discuss MSMEs financial literacy. Findings: Stage 1 results show that the financial literacy score of Greek MSME owners is 60.23%, very close to the adult population OECD (2020) percentage. In stage 2, we discuss the scores and survey results with stakeholders in focus groups and we get specific recommendations in the MSMEs financial literacy field, from an MSMEs policy perspective. Research limitations/implications: The main limitation of this study is the small sample of MSME owners that participated in the first stage of our methodological approach. The main practical implication of this paper is that the MSMEs stakeholders' bodies can offer useful insights in the MSMEs financial literacy field. Originality/value: This study contributes to the field of MSMEs financial literacy (FL) by suggesting an integrated approach in measuring the financial theory of MSMEs, by including both quantitative and qualitative data. We believe that, by suggesting the inclusion of qualitative data derived from the MSMEs stakeholders' bodies, to complement the quantitative outcome via the application of the OECD structured questionnaire, we can reach better conclusions regarding the MSMEs FL field.
Keywords: G53; 330; MSMEs; financial literacy; survey; qualitative